Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes